2015
DOI: 10.1371/journal.pone.0124157
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Estimates of Coancestry, Inbreeding and Effective Population Size in the Spanish Holstein Population

Abstract: Estimates of effective population size in the Holstein cattle breed have usually been low despite the large number of animals that constitute this breed. Effective population size is inversely related to the rates at which coancestry and inbreeding increase and these rates have been high as a consequence of intense and accurate selection. Traditionally, coancestry and inbreeding coefficients have been calculated from pedigree data. However, the development of genome-wide single nucleotide polymorphisms has inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 51 publications
8
41
0
Order By: Relevance
“…The very close matches between N e (DF), N e (LD) and N e (ROH) (79.4, 74.4 and 70.0, respectively) calculated by Rodriguez-Ramilo et al (2014) for Spanish Holstein cattle may reflect the use of Holstein in designing the 50 K SNP chip that was used. Similarly, the first formal study of congruence of methodologies in pigs (Saura et al, 2015) gave N e (LD) 20.8 ±3.7 and N e (DF) 21.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The very close matches between N e (DF), N e (LD) and N e (ROH) (79.4, 74.4 and 70.0, respectively) calculated by Rodriguez-Ramilo et al (2014) for Spanish Holstein cattle may reflect the use of Holstein in designing the 50 K SNP chip that was used. Similarly, the first formal study of congruence of methodologies in pigs (Saura et al, 2015) gave N e (LD) 20.8 ±3.7 and N e (DF) 21.…”
Section: Discussionmentioning
confidence: 76%
“…There have been relatively few studies giving direct comparisons, within specific breeds, of genealogy-and LD-based estimates of N e (but see, e.g. Flury et al, 2010;Rodriguez-Ramilo et al, 2014;Bohmanova et al, 2015 with cattle;Hasler et al, 2011, horses;Saura et al, 2015, pigs). Although some studies show a close convergence, in others there are large disparities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, F coefficients estimated using allele frequencies (F HOM ) showed Genome structure in Barbaresca sheep breed considerable variation within the breed with respect to the other estimates (F ROH and F i ) and had the highest CV. Molecular inbreeding (F i ) and molecular coancestry (f ij ) coefficient values were much higher than the other coefficients because these two methods (which are obtained on a SNP-by-SNP basis) do not discriminate between alleles that are identical by descent (IBD) or IBS (Rodríguez-Ramilo et al, 2015). Moreover, the strong correlation between the pedigree inbreeding coefficient and the sum of ROH reported by several authors (Purfield et al, 2012) indicates that the estimates of F ROH are a good reflection of IBD and suggests that, in the absence of an animal's pedigree data, as may be the case for local endangered breeds, the extent of a genome under ROH may be used to infer aspects of recent population history, even from relatively few samples.…”
Section: Discussionmentioning
confidence: 95%
“…Leroy et al [29] demonstrated variation in N e estimates using different approaches. For Holsteins, N e estimates range from 50 [30] to 150 [31], with many intermediate estimates in between [32–35]. Estimates for Jerseys range from 73 [34] to 135 [33].…”
Section: Resultsmentioning
confidence: 99%